A natural compound (LCA) isolated from Litsea cubeba inhibits RANKL-induced osteoclast differentiation by suppressing Akt and MAPK pathways in mouse bone marrow macrophages. (15th July 2020) - Yu, Luyao; Jia, Dan; Feng, Kunmiao; Sun, Xiaolei; Xu, Wumu; Ding, Luying; Xin, Hailiang; Qin, Luping; Han, Ting
Abstract: Ethnopharmacological relevance: Litsea cubeba (Lour.) Pers. has been traditionally used as a folk prescription for treating rheumatic diseases in China. Aim of the study: This study aimed to investigate the effects and underlying mechanism of LCA, a new type of dibenzyl butane lignin compound extracted from L. cubeba, on macrophage colony stimulating factor (M-CSF) plus receptor activator of NF-κB ligand (RANKL)-induced osteoclast differentiation in mouse-derived bone marrow macrophages (BMMs). Material and methods: TRAP staining, TRAP enzyme activity assay and actin ring staining were applied to identify the effects of LCA on osteoclast differentiation. Protein expression of NFATc1, c-Fos and MMP-9, and phosphorylation of p65, Akt, JNK, ERK and p38 in RANKL-induced osteoclasts was determined using western blotting to investigate the underlying mechanism. Results: LCA significantly suppressed RANKL-induced osteoclast differentiation by inhibiting TRAP activity, decreasing the number of TRAP + multinuclear osteoclasts and reducing the formation of F-actin ring without obvious cytotoxicity in BMMs. Moreover, LCA treatment strongly reduced protein expression of NFATc1, c-Fos and MMP-9, and attenuated the phosphorylation of p65, Akt, JNK, ERK and p38 in RANKL-stimulated BMMs. Conclusions: LCA ameliorated RANKL-induced osteoclast differentiation via inhibition of Akt and MAPK signalings in BMMs, and may serve as a potential pro-drug for bone destruction prevention. Highlights: The anti-osteoclastogenic effect of LCA and the underlying mechanism of action were investigated for the first time. LCA, a new type of dibenzyl butane lignin compound extracted from L. cubeba, has a rather different structure from the available anti-RA drugs. LCA inhibits osteoclast differentiation by regulating Akt and MAPK signalings. LCA may be a potential prodrug to prevent bone destruction.